90+x*291=91

Simple and best practice solution for 90+x*291=91 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90+x*291=91 equation:


Simplifying
90 + x * 291 = 91

Reorder the terms for easier multiplication:
90 + 291x = 91

Solving
90 + 291x = 91

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-90' to each side of the equation.
90 + -90 + 291x = 91 + -90

Combine like terms: 90 + -90 = 0
0 + 291x = 91 + -90
291x = 91 + -90

Combine like terms: 91 + -90 = 1
291x = 1

Divide each side by '291'.
x = 0.003436426117

Simplifying
x = 0.003436426117

See similar equations:

| 3x-9-12=3 | | v-9=-7v+7 | | 1-1/5= | | 4x^2+48x+108=0 | | 3(8x-4)=6(4x-2) | | [x]-14=21 | | 3x+2+5x=15+4x-4+7 | | (4x+3y)=180 | | 3m+15=42 | | 2m-13=-8m+27 | | M^2=74 | | 3(4x+6)=12x+20 | | 30-5x=120-25x | | 13x+15+20x=180 | | x=-0.333333333333 | | ln(x^8)ln(x^6)=2 | | 11x-12=5x-6 | | -6m-8=24 | | -7(21-2y)+2y=-3 | | 50-k=10 | | logx=5.43 | | 8x+4=7x-19 | | (2x+2)(z^5-3)+6=0 | | 13x+15=20x | | 12(2x-7)=6(6x+4) | | 7v-4v=6 | | 18x+32=2x | | 1.28x+4.34=8.67 | | -7s-9+11s=-5+4s-4 | | X-9y=81 | | 3x+2+x+-6=25 | | 23-11=35c |

Equations solver categories